Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Karyawan Pada HOKIbank Bali - Pramana, Agus Herry; Kusdyah, Ike; Alamsyah, Agus Rahman (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
HOKIbank is one of the many banks, especially the Rural Bank, which do business on the island of Bali. The phenomenon that occurred was during the Covid-19 pandemic, the economy in Bali in general and in particular the banking sector experienced a fairly drastic decline, and HOKIbank on the other hand experienced a very significant growth. This development is certainly influenced also by internal factors. The purpose of this study is to find out and analyze 1) the influence of leadership on employee satisfaction, 2) the influence of organizational culture on employee satisfaction, 3) the influence of leadership on employee performance, 4) organizational culture on employee performance, 5) the effect of employee satisfaction on employee performance, 6) the influence of leadership on employee performance through employee satisfaction, 7) the influence of organizational culture on employee performance through employee satisfaction. This research is categorized as causal associative research with a quantitative technique using a survey approach. This study was conducted on HOKIbank employees at its Denpasar head office and all Denpasar, Tabanan and Gianyar branch offices. The population in this study was all permanent employees at the beginning of November 2022 with a saturated sample of 103. The survey result was analyzed with SmartPLS 4.0.8.4 (2022). The results showed that 1) leadership directly affects employee satisfaction, 2) organizational culture directly affects employee satisfaction, 3) leadership does not directly affect employee performance, 4) organizational culture directly affects positive and significant affects employee performance or leadership employee performance, 5) employee satisfaction directly affects positive and significant employee performance, 6) leadership has a positive and significant effect on employee performance through full mediation, 7) organizational culture has a positive and significant effect on employee performance through partial mediation.